2022
DOI: 10.1128/jcm.02443-21
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Detection of Latent Mycobacterium tuberculosis Infection by Combined Heparin-Binding Hemagglutinin (HBHA) and Early Secreted Antigenic Target 6 (ESAT-6) Whole-Blood Interferon Gamma Release Assays

Abstract: Optimal detection of latent tuberculosis (TB) infection (LTBI) remains a challenge, although it is essential to reach the goal of TB elimination. Our objective was to develop and clinically evaluate a user-friendly, 24-h, whole-blood (WB) interferon gamma (IFN-γ) release assay (IGRA) improving the detection of LTBI, compared to available tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It is of note that, except for one patient, mediastinal TBLA was characterized by very high IFN-γ responses to ESAT-6, associated to positive responses to HBHA, albeit lower than those to ESAT-6 ( Table 4 ). Such IGRA profiles were previously reported to be highly suggestive of active TB, whereas the reverse profile (high response to HBHA with low or absent response to ESAT-6) is suggestive of LTBI [ 7 , 8 , 9 , 10 , 11 , 13 , 14 , 15 ]. Finally, the HBHA/ESAT-6 IGRA was positive for the three patients with disseminated TBLA (group 3) with a profile highly suggestive of active TB ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is of note that, except for one patient, mediastinal TBLA was characterized by very high IFN-γ responses to ESAT-6, associated to positive responses to HBHA, albeit lower than those to ESAT-6 ( Table 4 ). Such IGRA profiles were previously reported to be highly suggestive of active TB, whereas the reverse profile (high response to HBHA with low or absent response to ESAT-6) is suggestive of LTBI [ 7 , 8 , 9 , 10 , 11 , 13 , 14 , 15 ]. Finally, the HBHA/ESAT-6 IGRA was positive for the three patients with disseminated TBLA (group 3) with a profile highly suggestive of active TB ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 91%
“…IGRA results were strongly positive for the six patients with TBLA, with isolated IFN-γ secretion to ESAT-6 for one of them (patient n°7) and higher IFN-γ secretion in response to ESAT-6 than to HBHA for two others (patients n°3 and n°6) ( Table 4 and Figure 1 ). These IGRA profiles, which are highly suggestive of active TB [ 7 , 9 , 11 , 13 ], characterized patients with a unilateral cervical ADP (n°3), a miliary TB (n°6), and bilateral cervical ADPs with axillar ADP (n°7). The other patients with unilateral cervical ADP had lower IFN-γ secretion in response to ESAT-6 than to HBHA, a profile characteristic of patients who better control M. tuberculosis infection [ 9 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An HBHA-IGRA is an already well-known promising immunodiagnostic test, mainly designed for the detection of TB infection status and its differential diagnosis from PTB ( 10 , 14 , 19 , 21 ). HBHA is a surface-associated protein involved in adherence to epithelial cells, which has been shown to be required for extrapulmonary dissemination of Mtb ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the potential value of HBHA-IGRA as a biomarker to distinguish TB infection from pulmonary TB (PTB) ( 19 21 ). However, these studies have mainly focused on PTB.…”
Section: Introductionmentioning
confidence: 99%